Good and Product as Categories of Political Economy (UNWE Yearbook, 2015)
In this study a conceptual differentiation has been made between good and product as fundamental concepts of economic theory and practice, taking into consideration the fact that good is a broader phenomenon than product. A detailed systematization of good and product as well of the efficacy and effectiveness, associated with them, has been motivated. For the purpose six types of classifications have been applied: substantial, creative, functional, reproductive, material and systematic.The differentiation between tangible and intangible good has been refined. The difference between productive and non-productive labor has been outlined and the groups of goods and products for which creation labor is productive and those for which it is non-productive have been identified.The author has supported the unconventional view that labor in science, education and medical services is productive and therefore creates not only a new usefulness, but a new value. If his view is accepted, this will change the manner of measuring the gross domestic product, national income, added value and economic growth, as well the approach for defining the limit between primary distribution and re-distribution of income.The concepts which have been considered in this paper can be used both in the development of the political economy course and in the teaching of courses in microeconomics and macroeconomics in economic universities.